(untitled) (Baltic Journal of Sport and Health Sciences, 2016)
Background. Mouse strains differ in body and skeletal muscle mass. It is commonly believed that specific force is a constant value irrespective of muscle mass. We hypothesised that excessive muscle hypertrophy might compromise force output. Methods. We studied force generating capacity and muscle mass of isolated soleus (SOL) and extensor digitorum longus (EDL) muscles in 14–15-week-old males of C57BL/6J, BEH+/+ and DUH mice (n = 7 per strain). In addition, muscles of young (4–5 weeks old, n = 7 per strain) BEH+/+ and DUH mice were also studied. Specific forces were calculated as isometric tetanic force divided by the estimated physiological cross-section area (PCSA) of the muscles. Results. DUH strain generated lower specific force (p < .01– .001) than both C57BL/6J and BEH+/+ strains in SOL (110 ± 20 vs. 146 ± 28 and 164 ± 8 mN/mm 2 , respectively) and EDL muscles (74 ± 18 vs. 101 ± 19 and 95 ± 11 mN/mm 2 , respectively). There were no differences between muscles of young and adult mice (p > .05). C57BL/6J and BEH+/+ generated similar specific force. Conclusions. Our results show that body mass is not associated with reduction in specific force of skeletal muscles in mice. It seems that age did not affect specific force either. However, the heaviest DUH mice had lower specific force in both slow twitch SOL and fast twitch EDL compared to BEH+/+ and C57BL/6J mice. It appears that DUH strain could be a useful model in studying factors limiting specific force of skeletal muscle. Keywords: muscle hypertrophy, muscles mass, specific force, mice.